IMPACT ANALYSIS OF PSAK 73 IMPLEMENTATION ON THE FINANCIAL PERFORMANCE OF PT PLN (PERSERO) - Liza Julianti; Nugrahini Kusumawati; Efi Tajuroh Afiah; Aris Trismayadi Nurizki (Nindikayla Institute, 2023)
PSAK 73 is the latest lease accounting standard that began to be implemented in the financial year 2020 report adopted from IFRS 16. In PSAK 73, it regulates the recognition, measurement, presentation and disclosure of leases, especially for tenants, by only allowing the classification of leases as financing leases so that the assets and liabilities of the lease transactions are recognized in the financial statements, there are optional exceptions for short-term leases and leases whose underlying assets are of low value. The purpose of this study is to analyze the impact of the application of PSAK 73 on rent on the assessment of the company's financial performance by calculating using financial ratios. The method used is descriptive qualitative developed by Jaka Maulana and M. Rizal Satria (2021). The results of this study show that the Solvency Ratio consisting of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) has a decreasing impact and in the Profitability Ratio consisting of Return Â On Investment (ROI) and Return on Equity (ROE) has increased